2021
DOI: 10.1097/rli.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Computed Tomography for Detection and Characterization of Monosodium Urate, Calcium Pyrophosphate, and Hydroxyapatite

Abstract: Objectives: The aim of this study was to determine the diagnostic performance of dual-energy computed tomography (DECT) to detect and distinguish crystal deposits in a phantom. The primary objective was to determine the cutoff DECT ratio and the cross-sectional area (CSA) of a crystal deposit necessary to differentiate monosodium urate (MSU), calcium pyrophosphate (CPP), and calcium hydroxyapatite (HA) using DECT. Our secondary objective was to determine the concentration for limit of detection for MSU, CPP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Switching from DEI to DER would provide similar results with similar caveats, except for adapted reference ranges. Importantly, the reference ranges for DER and DEI must take into account both the DECT systems and acquisition protocols used (i.e., radiograph beam spectral separation), in addition to relying on crystal calibration phantoms, as recently demonstrated in a phantom study (23). The absolute number of HUs was removed and the density of cortical bone was added as a reference point, as for conventional CT.…”
Section: Resultsmentioning
confidence: 99%
“…Switching from DEI to DER would provide similar results with similar caveats, except for adapted reference ranges. Importantly, the reference ranges for DER and DEI must take into account both the DECT systems and acquisition protocols used (i.e., radiograph beam spectral separation), in addition to relying on crystal calibration phantoms, as recently demonstrated in a phantom study (23). The absolute number of HUs was removed and the density of cortical bone was added as a reference point, as for conventional CT.…”
Section: Resultsmentioning
confidence: 99%
“…Minimum cross-sectional diameter of MSU crystal deposits of approximately 0.8 mm was reported for 2 different dual-source DECT systems and different tube voltage combinations. 124 Comparable performance of crystal differentiation (MSU and HA) was reported for DE-EICT and PCCT. 125 Tse et al 126 reported 3-material decomposition with virtual monochromatic images that may be superior to commercially available 2-material decomposition and dual-thresholding in differentiating MSU and HA at low concentrations (lower limits for MSU detection 3.4 mg/dL, 13.3 mg/dL, and 65.2 mg/dL; rapid kV switching DECT).…”
Section: Musculoskeletal Ctmentioning
confidence: 90%
“…Only few studies focused on cross-platform conformity. Minimum cross-sectional diameter of MSU crystal deposits of approximately 0.8 mm was reported for 2 different dual-source DECT systems and different tube voltage combinations 124 . Comparable performance of crystal differentiation (MSU and HA) was reported for DE-EICT and PCCT 125 …”
Section: Musculoskeletal Ctmentioning
confidence: 96%
“…Using dual thresholds (i.e. dual-energy ratios) during DECT post-processing, targeted at the crystal of interest, would have allowed a more accurate quantification of MSU deposition volumes, as recently demonstrated in a phantom study [ 14 ]. However, the default settings were considered acceptable here for measuring the percentage change in MSU volumes over time.…”
Section: Discussionmentioning
confidence: 99%